A Cytoplasmic Form of Gaussia luciferase Provides a Highly Sensitive Test for Cytotoxicity. - Saori Tsuji; Tetsuya Ohbayashi; Kohji Yamakage; Mitsuo Oshimura; Masako Tada (PLoS ONE, 2016)
The elimination of unfavorable chemicals from our environment and commercial products requires a sensitive and high-throughput in vitro assay system for drug-induced hepatotoxicity. Some previous methods for evaluating hepatotoxicity measure the amounts of cytoplasmic enzymes secreted from damaged cells into the peripheral blood or culture medium. However, most of these enzymes are proteolytically digested in the extracellular milieu, dramatically reducing the sensitivity and reliability of such assays. Other methods measure the decrease in cell viability following exposure to a compound, but such endpoint assays are often confounded by proliferation of surviving cells that replace dead or damaged cells. In this study, with the goal of preventing false-negative diagnoses, we developed a sensitive luminometric cytotoxicity test using a stable form of luciferase. Specifically, we converted Gaussia luciferase (G-Luc) from an actively secreted form to a cytoplasmic form by adding an ER-retention signal composed of the four amino acids KDEL. The bioluminescent signal was >30-fold higher in transgenic HepG2 human hepatoblastoma cells expressing G-Luc+KDEL than in cells expressing wild-type G-Luc. Moreover, G-Luc+KDEL secreted from damaged cells was stable in culture medium after 24 hr at 37°C. We evaluated the accuracy of our cytotoxicity test by subjecting identical samples obtained from chemically treated transgenic HepG2 cells to the G-Luc+KDEL assay and luminometric analyses based on secretion of endogenous adenylate kinase or cellular ATP level. Time-dependent accumulation of G-Luc+KDEL in the medium increased the sensitivity of our assay above those of existing tests. Our findings demonstrate that strong and stable luminescence of G-Luc+KDEL in human hepatocyte-like cells, which have high levels of metabolic activity, make it suitable for use in a high-throughput screening system for monitoring time-dependent cytotoxicity in a limited number of cells.